Muscle volume alterations after first botulinum neurotoxin A treatment in children with cerebral palsy: a 6-month prospective cohort study - Alexander, C.; Elliott, Catherine; Valentine, J.; Stannage, K.; Bear, N.; Donnelly, C.; Shipman, P.; Reid, S. (Wiley-Blackwell Publishing Ltd., 2018)
Aim: This study aimed to track alterations in muscle volume for 6 months in children with cerebral palsy (CP) after the first exposure to botulinum neurotoxin A (BoNT-A), a commonly used focal spasticity treatment. Method: Eleven ambulant children (eight males, three females) with spastic CP, mean age 8 years 10 months (SD 3y 1mo) participated. Participants received injections to the affected gastrocnemius. The muscle volume of the gastrocnemius, soleus, tibialis anterior, and hamstrings was measured using magnetic resonance imaging. Muscle volume was normalized to bone length, and changes analysed relative to baseline. Assessments were conducted 1 week before, and 4 weeks, 13 weeks, and 25 weeks after BoNT-A treatment. Results: All children demonstrated positive clinical and functional gains. Muscle volume of the injected gastrocnemius was found to be significantly reduced at 4 weeks (-5.9%), 13 weeks (-9.4%), and 25 weeks (-6.8%). Significant increases in normalized soleus muscle volume were identified at each follow-up, while hamstrings showed significant increase at 4 weeks only. Interpretation: Absolute and normalized muscle volume of the injected muscle reduces after first BoNT-A exposure, and does not return to baseline volume by 25 weeks. Hypertrophy is seen in the soleus up to 25 weeks; the volume of the plantar flexor compartment is stable. What this paper adds: Muscle atrophy after first botulinum neurotoxin A (BoNT-A) exposure in children with cerebral palsy is noted. Mild BoNT-A-induced muscle atrophy is still apparent 6 months after BoNT-A exposure. Hypertrophy is evident in soleus after gastrocnemius BoNT-A exposure. Total plantarflexor volume is unchanged.